Effects Of Credit Information Sharing On Performance Of Savings And Credit Cooperative Societies In Kenya - Anjawo, Otiende Wellington; Makokha, Elizabeth Nambuswa (Archives of Business Research, 2019)
The purpose of the study was to analyse the effect of credit information sharing on the performance of Saccos in Kenya. The specific objective was; to identify the effect of credit rating on performance of saccos in Kenya, The study was anchored on Information Asymmetry Theory, Credit Rationing Theory and Transaction Cost Theory. The research used a descriptive survey research design. The population for this study was the 60 Saccos with head offices in Nairobi Kenya, from where the researcher targeted the credit managers as the respondents of the study. This study was a census survey. The study used both primary and secondary data. The primary data was collected through a questionnaire from the credit managers of the 60 Saccos while secondary data was retrieved from the SASRA’s Sacco supervision annual reports for the respective years. The quantitative data was analysed using both descriptive and inferential statistics. Both correlation and multiple linear regression analysis method were used to analyze the relationship between the study variables. The study findings showed that a significant positive relationship between credit rating and the performance of Saccos in Kenya (β = 0.719 and P value < 0.05). The study concluded that credit rating, played a significant role in enhancing the performance of Saccos in Kenya due to their centrality in the Saccos’ lending decisions. The study recommends that Saccos in Kenya should cross reference the information they hold about clients with information held by the CRBs in order to enhance their credit rating activities when evaluating a client’s suitability for loans applied. The study also recommends that Saccos in Kenya should review their lending policies to ensure that they promote timely repayment of monies given out as loans to various borrowers. The study will be of significance to many stakeholders; members/customers will both benefit from increased loanable funds as well as increased dividends. The government is likely to receive higher revenue arising from taxes while the citizenry may benefit from employment opportunities occasioned by a well performing Sacco.